Sistema automatizado para reposição de nutrientes e ajuste de pH em hidroponia - Moran, Mateus Henrique Roskosz (2022)
Population growth generates a greater demand for food. Therefore, it is necessary to seek alternative methods to traditional soil cultivation and create facilitators for those who produce a food base for society. This paper aimed to create a tool for use in hydroponic cultivation, considering that one of the main factors that determine the success and quality of hydroponic production is nutrient control and pH adjustment of the nutrient solution. This nutrient solution is responsible for plant growth, and if it is unbalanced, food production can lose quality. Based on this premise and using the concept of microcontrolled systems, this paper presents the design and prototyping of a functional module that allows the user to schedule corrective actions for a nutrient solution, such as pH adjustment and nutrient concentration. For this, an ATmega2560 microcontroller was used, LCD display for data presentation, matrix keyboard for data entry, HC-SR04 ultrasound sensors that acquires the water level and a 5 V water bomb to control the parameters of the nutrient solution. As a result, a functional prototype was obtained that allows the scheduling and configuration of applications in a simple way, editing date, time, periodicity and volume to be applied in the general reservoir of the simulated hydroponic system.